Synchronization of digital telecommunications networks - Bregni, Stefano (Wiley, 2002)
A co-ordinated treatise of the subject, from the basics to several advanced topics, this valuable reference resource presents the latest advances on the clock stability measurement techniques adopted in telecommunications.